PENGARUH PEMBERIAN EKSTRAK BUAH MENGKUDU (Morinda citrifolia) DALAM LARUTAN NATRIUM KLORIDA FISIOLOGIS SEBAGAI BAHAN PENGENCER SEMEN TERHADAP PENINGKATAN KUALITAS SPERMATOZOA AYAM BURAS PADA SUHU RUANG (Effect of Noni Extract Fruit (Morinda citrifolia) in Physiological Saline Solution as Diluent on the Native Chicken Spermatozoa Quality at Room Temperature) - Murcahyana, Murcahyana; Susilawati, Trinil; Isnaini, Nurul (Jurnal Kedokteran Hewan, 2016)
The purpose of this research was to analyse the quality and storability of native chicken semen at room temperature after diluted with physiological saline solution (NaCl) supplemented with noni fruit extract. Research methodology used was nested randomized design which variables observed covering the quality of chicken spermatozoa macroscopically and microscopically with the doses of noni fruit extract of 0 % (P0), 10 % (P1), 20 % (P2), and 30 % (P3). Rate of spermatozoa motility at 0, 1, 2, and 3 hours on P0 were 83.704.74, 63.309.63, 32.908.52, and 15.006.20; P1 were 85.305.44, 72.7010.06, 51.9011.75, and 28.505.68; P2 were 84.606.40, 78.508.59, 57.9010.73, and 33.709.06; and P3 were 81.807.30, 64.207.93, 40.3011.66, and 19.807.47, respectively. Rate of spermatozoa viability at 0, 1, 2, and 3 hours on P0 were 85.309.09, 65.106.15, 32.1011.86, and 10.309.09; P1 wer 87.406.22, 72.705.33, 50.8013.59, and 26.5010.99; P2 were 68.585.30, 77.704.79, 56.3013.76, and 32.7013.79; P3 were 81.208.04, 68.7010.40, 36.2016.61, and 16.9011.93, respectively. Rate of spermatozoa abnormality at 0, 1, 2, and 3 hours on P0 were 8.703.40, 12.204.42, 17.805.67, and 20.306.38; P1 were 7.802.04, 9.802.69, 13.604.45, and 16.505.19; P2 wer 8.404.33, 10.002.45, 12.505.21, and 15.803.71; and P3 were 9.603.41, 10.902.64, 17.105.61, and 21.208.16, respectively. It can be concluded that the addition of noni fruit extract at the dose of 10 % and 20 % in physiological saline solutin maintain the native chicken spermatozoa quality up to 2 hours post storage at room temperature.